ANALISIS KONSERVASI KURATIF KOLEKSI TERCETAK BUNG HATTA DI UPT. PERPUSTAKAAN PROKLAMATOR BUNG HATTA BUKITTINGGI - Ananda, Dea Rafnita; Wahyuni, Sri; Safri, T. Mulkan; Ikhwan (Program Studi Ilmu Perpustakaan, Fakultas Adab dan Humaniora Universitas Islam Negeri Ar-Raniry Banda Aceh, 2025)
This study aims to analyze the curative conservation of Bung Hatta’s printed collection at the Technical Implementation Unit (UPT) of the Proclamator Bung Hatta Library in Bukittinggi. The collection holds significant historical and intellectual value but faces deterioration risks due to age, storage conditions, and limited resources. The research employs a qualitative narrative approach through observation, in-depth interviews, and documentation. The findings reveal that curative conservation is conducted systematically through stages such as damage identification, cleaning, conservation treatments including deacidification, manual mending, lamination, and rebinding. However, several challenges remain, including limited budgets, inadequate facilities, a shortage of conservation experts, and the absence of post-conservation monitoring. Additionally, users’ careless handling of materials contributes to further damage. To overcome these barriers, the library has made efforts to enhance conservator training, use alternative conservation tools, strengthen collaboration with other institutions, and provide education for both librarians and users on proper collection care. This study highlights the importance of curative conservation as a key strategy in preserving historically valuable library materials to ensure their accessibility for future generations. With proper management and supportive policies, the conservation of Bung Hatta’s collection can be sustained. These efforts also reflect the library’s commitment to safeguarding national cultural heritage and reinforcing its role as a center of historical literacy. Keywords: Curative Conservation; Printed Collection; Bung Hatta library; Preservation; Cultural Heritage.